English as the Academic Lingua Franca (ELFA) for research publication purposes: voices from Iraq and Turkey - Alhasnawi, Sami; Uysal, Hacer Hande; Selvi, Batuhan (Walter de Gruyter Gmbh, 2023)
This paper contributes to the recently increasing literature on the role of English as the Academic Lingua Franca (ELFA) in international research publications, and the potential pros and cons this may entail for non-Anglophone scholars in different contexts. While exploring Turkish and Iraqi scholars' attitudes to English for research publication purposes (ERPP), their research writing challenges, and the strategies they use for successful publication, which are areas still lagging far behind in the current state of research, will be the main focus. Therefore, an online questionnaire was designed in this context to investigate the experience of academicians of different academic ranks across university disciplines in both Turkey and Iraq to address such a research gap. Findings are expected to enrich the field with respect to the presumed relationship between ELFA and 'linguistic injustice/hegemony', problems encountered by non-Anglophone scholars in different contexts, and their strategies for successful publication through English.
Keywords: English as the Academic Lingua Franca (ELFA); international visibility; research policy; research publication challenges and strategies; writing for publication purposes; English spread